2003
DOI: 10.1002/cbf.1047
|View full text |Cite
|
Sign up to set email alerts
|

Liver denervation affects hepatocyte mitochondrial fatty acid transport capacity

Abstract: The effect of liver denervation on the activity of hepatic carnitine palmitoyltransferase (CPT) system, which catalyses the transfer of long-chain fatty acids into the mitochondria, was studied in rats. Noradrenaline content in phenol-denervated liver (D) was reduced by 87%. CPT I and II activities (measured by radioassay after detergent separation of the enzymes) were decreased (p < 0.001) in D (2.6 +/- 0.1 and 0.68 +/- 0.2 nmol min(-1) mg(-1) protein, respectively) as compared with controls (4.7 +/- 0.3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 47 publications
5
21
0
Order By: Relevance
“…The activity of the enzyme CPT I is the principal site of regulation of oxidation. 44 A decrease in the expression of this enzyme in denervated animals is herein reported, in agreement with our previous results that showed a decrease in the activity of this enzyme, 20 reducing the availability of fatty acids for oxidation. Therefore, in denervated animals, these fatty acids are available to follow other pathways, as for instance, the synthesis of cholesterol, as we demonstrated a slight increase in hepatic cholesterol concentration, related to the altered expression of ACAT.…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…The activity of the enzyme CPT I is the principal site of regulation of oxidation. 44 A decrease in the expression of this enzyme in denervated animals is herein reported, in agreement with our previous results that showed a decrease in the activity of this enzyme, 20 reducing the availability of fatty acids for oxidation. Therefore, in denervated animals, these fatty acids are available to follow other pathways, as for instance, the synthesis of cholesterol, as we demonstrated a slight increase in hepatic cholesterol concentration, related to the altered expression of ACAT.…”
Section: Discussionsupporting
confidence: 95%
“…4,25 Previous studies in our laboratory had already shown that hepatic denervation alters lipid metabolism in the organ, leading towards lower oxidation of fatty acids and decreased incorporation into VLDL. 20 It is known that catecholamines play a role in the regulation of VLDL secretion, 17,19,26 but no studies, to our knowledge, have so far examined the importance and contribution of the sympathetic innervation to the process. Our results show a lower secretion of VLDL in the denervated animals compared with controls, which was related with a lower expression of apoB in these.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, also central GLP-1 infusion decreased hepatic TG content and expression of lipogenic enzymes in mice, suggesting that GLP-1 can at least in part affect hepatic TG metabolism via a central mechanism ( 38,39 ). In addition, in vitro activation reduced incorporation of exogenously administered fatty acids into the plasma VLDL-TG fraction ( 27 ), pointing to decreased VLDL-TG secretion. Accordingly, Bruinstroop et al ( 28 ) recently showed that hepatic sympathetic denervation in rats reduced hepatic VLDL-TG secretion.…”
Section: Anatomy Of Hypothalamic Sympathetic Outflowmentioning
confidence: 95%